2015
DOI: 10.1007/s12026-015-8644-2
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with lipopolysaccharide attenuates diethylnitrosamine-caused liver injury in mice via TLR4-dependent induction of Kupffer cell M2 polarization

Abstract: In this study, we found that pretreatment with low dose of lipopolysaccharide (LPS), also known as lipoglycans and endotoxin, obviously attenuated liver injury caused by diethylnitrosamine (DEN) in mice. This protective effect was described by decreased ALT, TNF-α, and IL-1β and increased TGF-β production. However, Toll-like receptor 4-deficient (TLR4(-/-)) or macrophages depletion abolished this protection in mice, which revealed Kupffer cells (KCs) and TLR4 to be crucial for the prevention of LPS against DEN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Accordingly, our data suggested that the inflammatory response was aggravated to defend against SIV infection, and IL-10 decreased and was not enough for the maintenance of homeostasis and immunity, thereby reducing the tolerance and increasing viral replication. On the contrary, excessive inflammatory responses can induce anti-inflammatory responses ( 19 ), and M2 macrophage polarization (anti-inflammatory macrophage phenotype) is TLR4 dependent ( 45 ). Therefore, it is likely that AFB 1 promotes SIV replication via the TLR4-dependent induction of M2 macrophage polarization, but this possibility needs to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, our data suggested that the inflammatory response was aggravated to defend against SIV infection, and IL-10 decreased and was not enough for the maintenance of homeostasis and immunity, thereby reducing the tolerance and increasing viral replication. On the contrary, excessive inflammatory responses can induce anti-inflammatory responses ( 19 ), and M2 macrophage polarization (anti-inflammatory macrophage phenotype) is TLR4 dependent ( 45 ). Therefore, it is likely that AFB 1 promotes SIV replication via the TLR4-dependent induction of M2 macrophage polarization, but this possibility needs to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…Although the liver is constantly exposed to LPS from the intestinal microflora, inflammation is not apparent in the healthy liver because of an immunological adaptation process called hepatic tolerance [37]. Recently, it has been shown that low doses of LPS pretreatment attenuated the liver injuries induced by diethylnitrosamine via TLR4 participation in mice and this phenomenon was associated to hepatic tolerance [38]. Additionally, upon LPS stimulation, LPS binds to TLR4 and induces both the recruitment of MYD88 to TLR4 to regulate inflammation by the activation of NF-κB transcription factor and, the interaction of FLII with MYD88 through NXN to avoid the undesirable activation [10].…”
Section: Discussionmentioning
confidence: 99%
“…LPS and TLR4 signaling promote M2-like polarization of KCs, which promotes endotoxin tolerance and protects from liver injury by preventing pro-inflammatory cytokine production and the attraction of Treg to the liver. 62 Of note, M2-polarized KCs apparently can also promote selective apoptosis of classical, M1-polarized KCs in alcoholic hepatosteatitis (ASH), a process that involves the paracrine induction of arginase, an M2 marker, via IL-10 secretion in the inflammatory local microenvironment, 63 thereby acting to restore homeostasis. Apart from these anti-inflammatory effects, antigen engulfment by KCs can directly contribute to the induction of local but also systemic tolerance: KCs can elicit CD4 + T-cell arrest of passenger leukocytes and T-cell proliferation, and the secretion of IL-10 induces expansion and activation of CD4 + CD25 + Foxp3 + Treg.…”
Section: Antigen-presenting Cells In the Liver And Their Function In mentioning
confidence: 99%